Зарубіжний досвід впровадження CBDC - Бєляєва, Ангеліна Віталіївна; Byelyayeva, Anhelina Vitaliyivna (Ірпінь, 2024)
Розкрито сутність та перспективи впровадження цифрової валюти центральних банків. Охарактеризовано правове регулювання запровадження цифрової валюти центрального банку (CBDC) та правового регулювання цифрових грошей в Україні. Оцінено внутрішні детермінанти цифрових валют в Україні. Проаналізовано можливості впровадження світового досвіду цифрової валюти центрального банку в Україні. Визначено загрози та можливості використання цифрових валют в Україні.

The essence and prospects of the introduction of digital currency are revealed central banks. The legal regulation of the introduction of the central bank digital currency (CBDC) and legal regulation of digital money in Ukraine is characterized. The internal determinants of digital currencies in Ukraine are evaluated. The possibilities of implementing the global experience of the digital currency of the central bank in Ukraine were analyzed. The threats and opportunities of using digital currencies in Ukraine have been identified.
Foreign experience of CBDC implementation
Keywords: цифрова валюта центрального банку; криптовалюта; платіжна система; центральний банк; емітент; майнінг; central bank digital currency (CBDC); cryptocurrency; payment system; central bank; issuer; mining